2020
DOI: 10.3390/molecules25153553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymus vulgaris L., Cinnamomum verum J.Presl and Cymbopogon nardus (L.) Rendle Essential Oils in the Endotoxin-induced Acute Airway Inflammation Mouse Model

Abstract: Thyme (TO), cinnamon (CO), and Ceylon type lemongrass (LO) essential oils (EOs) are commonly used for inhalation. However, their effects and mechanisms on inflammatory processes are not well-documented, and the number of in vivo data that would be important to determine their potential benefits or risks is low. Therefore, we analyzed the chemical composition and investigated the activity of TO, CO, and LO on airway functions and inflammatory parameters in an acute pneumonitis mouse model. The components of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
(67 reference statements)
0
14
0
1
Order By: Relevance
“…ΚΕGG analysis demonstrated the enrichment of hub genes in cancer as well as infection pathways, which corroborated the antiinflammatory role of HYJJ. In the formula, combating inflammation was the principal target accomplished by eight herbs, such as ACD, ZR, GF, PGM (Jin et al, 2020), PB (Tian et al, 2020), SCF (Li et al, 2020;Li et al, 2021), PCW as well as CC (Csikos et al, 2020). In addition to inflammation, the recovery of gut motility and orchestration of the gut innervation were also underlined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ΚΕGG analysis demonstrated the enrichment of hub genes in cancer as well as infection pathways, which corroborated the antiinflammatory role of HYJJ. In the formula, combating inflammation was the principal target accomplished by eight herbs, such as ACD, ZR, GF, PGM (Jin et al, 2020), PB (Tian et al, 2020), SCF (Li et al, 2020;Li et al, 2021), PCW as well as CC (Csikos et al, 2020). In addition to inflammation, the recovery of gut motility and orchestration of the gut innervation were also underlined.…”
Section: Discussionmentioning
confidence: 99%
“…Among these herbs, the combination of ACD, ZR and GF also termed by Si-Ni decoction has shown proven efficacy for septic shock (Chen et al, 2011), sepsis (Brislinger et al, 2018;Zeng et al, 2019) by interfering with apoptosis and inflammatory responses (Aly et al, 2005;Endo et al, 2017;Yang et al, 2017;Endo et al, 2018;Bai et al, 2020). In the context of SI-NI decoction, the anti-inflammatory function has been emphasized by the addition of PGM (Jin et al, 2020), PB (Tian et al, 2020), SCF (Panossian & Wikman, 2008;Li et al, 2020;Li et al, 2021), PCW as well as CC (Csikos et al, 2020). Moreover, focusing on the impaired gastrointestinal functions, AMK is included to improve gastrointestinal motility (Zhu et al, 2018;Yang et al, 2019) and restore immune homeostasis (Xiang et al, 2020), while CR maintains homeostasis of the gut microbiota (Chen et al, 2020) and inhibits inflammation (Ho & Lin, 2008;Herath et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Carvacrol is below 3%. [63] reported that thymol (46.3%) and p-cymene (22.1%) were identified as the main components of TEO. Rinaldi et al [64] showed the presence of thymol as the most abundant (44.4%) followed by O-cymene (18.2%) and linalool (7.5%) in the chemical composition of TEO.…”
Section: The Chemical Composition Of the Thymus Vulgaris Essential Oilmentioning
confidence: 99%
“… Inflammatory airway hyperresponsiveness and certain cellular inflammatory parameters were reduced. [66] 18 70% aqueous ethanol bark In vitro/in vivo monocyte-derived mature dendritic cells /immunized- BALB/c mice with ovalbumin 1 mL/kg body weight/every other day/ 23 days DC maturation and subsequent allergen-specific T cell proliferation and Th1 and Th2 cytokine production were inhibited. Sulphidoleukotriene release and CD63 expression by basophils were diminished.…”
Section: Potential Pharmacological Effects Of Cinnamon Against Covid-19mentioning
confidence: 99%
“…Patient autopsy shows epithelial exfoliation and hyperplasia, mucosa congestion, alveolar damage, exudative inflammation, and thrombosis in infected lungs [80] . Inhalation of Cinnamon essential oil (with cinnamaldehyde as the main ingredient) improves respiratory functions and inflammatory conditions in lipopolysaccharide-induced airway inflammation [66] . Type-A procyanidin polyphenols (TAPP) from Cinnamomum zeylanicum exhibited anti-asthmatic and anti-inflammatory effects in ovalbumin-induced airway hyperresponsiveness animal models.…”
Section: Potential Pharmacological Effects Of Cinnamon Against Covid-19mentioning
confidence: 99%